2021
DOI: 10.1021/acs.iecr.1c02007
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-Based Materials for the Removal of Contaminants from Wastewater: A Review

Abstract: Water pollution from the continuous disposal of hazardous substances has become a serious issue and a global concern for the environment and public health. Removal of these pollutants from water is an ongoing challenge, and several approaches have been proposed and applied for this purpose. Adsorption is one of the common and most efficient approaches often used because it is simple, quick processing, inexpensive, and eco-friendly. Polyoxometalates (POMs) are a well-known class of metal–oxygen cluster compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 85 publications
(176 reference statements)
0
27
0
Order By: Relevance
“…The purification of wastewater from dye contaminants has become one of the intensively studied processes, and recent reviews , reported the perspective on the use of POM-based compounds for this purpose. As it was shown in numerous studies, the main process of the removal of organic dyes from water is photocatalytic degradation. The works where compounds acted as adsorbents were far fewer. , Previously, we reported the Strandberg-based complex activity toward the adsorption of cationic dye methylene blue (MB) for the first time . Compounds 1 and 2 were chosen as suitable candidates to continue this study due to their very low solubility in water and to compare their sorption ability depending on the type of POM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purification of wastewater from dye contaminants has become one of the intensively studied processes, and recent reviews , reported the perspective on the use of POM-based compounds for this purpose. As it was shown in numerous studies, the main process of the removal of organic dyes from water is photocatalytic degradation. The works where compounds acted as adsorbents were far fewer. , Previously, we reported the Strandberg-based complex activity toward the adsorption of cationic dye methylene blue (MB) for the first time . Compounds 1 and 2 were chosen as suitable candidates to continue this study due to their very low solubility in water and to compare their sorption ability depending on the type of POM.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 Sorption Properties. The purification of wastewater from dye contaminants has become one of the intensively studied processes, and recent reviews 54,55 reported the perspective on the use of POM-based compounds for this purpose. As it was shown in numerous studies, the main process of the removal of organic dyes from water is photocatalytic degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dodecamolybdophosphate and dodecatungstophosphate are among the most known and studied polyoxometalates (POMs) due to their important properties valuable for many applications in various fields of research such as catalysis, , energy, , biology, and the environment. , This class of highly soluble metal-oxo clusters was first discovered by Berzelius in the early 19th century, but their structure was not determined until more than 100 years later by Keggin . The heteropolyanion is composed of a metal-oxo shell containing 12 MO 6 polyhedra (M = Mo VI or W VI ) connected together that defined a central tetrahedral cavity in which a phosphorus atom P V is located (Figure a), leading to a general chemical formula PM 12 O 40 3– , hereafter abbreviated as {PM 12 }.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Fukushima-Daiichi nuclear accident and the subsequent decision to release nuclear wastewater into the ocean, the international community has shown growing concern about radionuclide-related environmental pollution. , Polyoxometalates (POMs) are polynuclear metal–oxygen cluster compounds that are structurally diverse, designable, and soft, and almost all of the metal and non-metal elements could be introduced into POMs. Thus, POMs have shown promise for controlling radionuclide pollution. Due to the unique features of 5f electrons, actinides always show abundant oxidation states and are well self-assembled members of POMs. The obtained actinide-containing POMs may exhibit fascinating structures and properties, which may promote the development of the enrichment of radionuclides, separation and immobilization of spent fuel, and studies of the migration behavior of actinides. , Moreover, the study of actinide-containing POMs may also provide insight into the geochemical processes and new decontamination approaches. …”
Section: Introductionmentioning
confidence: 99%